Strategic approaches to sustainable fisheries management in west aceh district: integrating the code of conduct for responsible fisheries - M.A. Chaliluddin; Caya Anggun; Jasmudin Meilinda; Djamani Rianjuanda; Junaidi M. Affan; Roesa Nellyana; Aditya Rivaldi; Rahmat Rizqi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Aceh is a province located in the western part of Indonesia, and most of its region is a coastal area that faces rapid population growth, which puts pressure on sectors like fisheries and marine resources. One of those is the West Aceh District the location of this research. Capture fisheries represent a crucial economic sector for the livelihoods of many communities, provided it is well-managed. One of the important factors contributing to the decline in fish populations is the use of environmentally harmful fishing gear. This paper aims to determine a strategy for environmentally- friendly capture fisheries management based on the code of conduct for responsible fisheries in West Aceh District, which is crucial for protecting aquatic habitat sustainability and future fish stock populations. A descriptive method combined with a survey was conducted during the research and SWOT was used as a data analysis method. The result is several important measures should be implemented in Aceh Barat District based on the code of conduct for responsible fisheries, from providing enough information and training for fishermen to enhance their knowledge and skills on sustainable fisheries management, to constructing representative fishing ports is also necessary to support efficient and environmentally friendly fishing activities, lastly, maximising the monitoring of fishing gear usage that meets the environmental standards and strengthening the law enforcement.Keywords:Strategic approachesSustainable fisheriesCCRFWest AcehMeulaboh